2016
DOI: 10.11607/jomi.4618
|View full text |Cite
|
Sign up to set email alerts
|

Internal- vs External-Connection Single Implants: A Retrospective Study in an Italian Population Treated by Certified Prosthodontists

Abstract: The design of an implant connection that allows prosthetic suprastructures to be attached to implants has long been debated in the dental literature. The goal of this retrospective study was to evaluate the 5-year clinical results for a large number of single implants restored by certified prosthodontists in an attempt to establish whether different clinical outcomes could be detected for external-or internalconnection implants. Materials and Methods: All single implants with internal or external connections i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
2
16
0
3
Order By: Relevance
“…There are also studies stating that the difference in connection types does not have a significant influence on screw loosening. Vigolo et al compared the two connection types by a retrospective study. In a follow‐up period of at least 5 years involving 2010 implants in 1159 patients, no significant difference was found in the incidence of screw loosening between two connections, which was similar to the result of Chae et al However, many other factors may also affect the results in clinical practice.…”
Section: The Factors Contributed To Abutment Screw Looseningsupporting
confidence: 81%
“…There are also studies stating that the difference in connection types does not have a significant influence on screw loosening. Vigolo et al compared the two connection types by a retrospective study. In a follow‐up period of at least 5 years involving 2010 implants in 1159 patients, no significant difference was found in the incidence of screw loosening between two connections, which was similar to the result of Chae et al However, many other factors may also affect the results in clinical practice.…”
Section: The Factors Contributed To Abutment Screw Looseningsupporting
confidence: 81%
“…The problem is often encountered in external hexagon implants during the first 2 years from the placement of the prosthetic restoration, while specific reference is made regarding the screw loosening in single external hexagon implants than in similar implants with internal connection . Nevertheless, it is worth mentioning that in other in vitro and in vivo studies, it was reported that internal connection showed no advantage regarding screw loosening compared to external connection. It should be mentioned, however, that, although the clinical trials included a great number of patients and implants, the treating clinicians were certified prosthodontists and the outcomes should be interpreted with caution as they may not represent the clinical reality of a wide number of practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,24,31,32 The problem is often encountered in external hexagon implants during the first 2 years from the placement of the prosthetic restoration, 22 while specific reference is made regarding the screw loosening in single external hexagon implants than in similar implants with internal connection. 11 Nevertheless, it is worth mentioning that in other in vitro 33,34 and in vivo studies, 35,36 it was reported that internal connection showed no advantage regarding screw loosening compared On the other hand, some studies 25,37,38 support the superiority of the conical connection over the internal and the external hexagon, as the micro-motions of the prosthetic abutment, the expanding of the micro-gaps under pressure and the industrial stability are concerned. 39 The conical connection (Figure 21) is the type of internal connection that minimizes the gap between implant and prosthetic abutment with In the majority of clinical studies, technical problems occurred more frequently in screw-retained restorations (57%) compared to cement-retained (22.8%), with most common the loosening of the fixing screw of the abutment.…”
Section: Internal or External Connection Of Implant-abutmentmentioning
confidence: 96%
“…After reviewing the titles and abstracts of the manuscripts and applying the inclusion/exclusion criteria, 23 studies were eligible for further analysis. After reading these studies, 12 were excluded as they were retrospective studies [24][25][26][27][28][29][30][31][32] or had their data included in other articles with longer follow-ups [33][34][35] Altogether, 11 studies were selected for this systematic review [2,4,34,[36][37][38][39][40][41][42][43][44] Fig. 1 depicts a flow diagram detailing the search strategy.…”
Section: Literature Searchmentioning
confidence: 99%